1837 .M (1253 H.) TARİH VE 20 NUMARALI KÜTAHYA ŞER?İYYE SİCİLİ - DEMİRKOL, MEHMET (Fırat Üniveristesi, 2016)
Bu çalışmada 1837 M. (1253 H.) Tarih ve 20 Numaralı Kütahya Şer?iyye Sicili'ni çevirmeye çalıştık. Çünkü tarih araştırmalarında Osmanlı Devleti döneminden günümüze intikal eden bu belgelerin ilk elden kaynak olduğunun bilinci içerisindeyiz. Tez dört bölümden oluşur. 422 belgeden oluşan sicilde çeviri ve değerlendirmenin yanı sıra kadılık kurumu ve şer?iyye sicili hakkında bilgi verilir. Bu çalışma hicri 1250 yılı Kütahya'nın ekonomik ,idari, sosyal ve hukuki yönünü sunmak amacı ile yapılmıştır.

In this study, we tried to turn the Shar'iyyah Registry of Kütahya 1837 M. (1253 H.) the dated and 20 numbered. Because we awake that these documents are the primary source inherited from Ottoman Empire period to present day in history researches. Thesis consists of four chapters. In the Registry that consisted from 422 documents is given information about Kadi Institute and Shar'iyyah Registries as well as translation and evaluation. This study is carried out in order to present the history of Kütahya economic, administrative, social and legal aspects in 1253 Hijri the year.
1837 M.(1253 H.) date the 20 numbered Kütahya Şer?iyye Sicili
Keywords: Tarih